Proceso de ASC - OPERA HOSPITAL MENTAL. OPERA DEL TERROR. PARTE 1 (2023)
Creation of a horror opera based on events that occurred in a mental hospital. Presented in an unconventional warehouse-style setting, where the audience will be immersed in the performance through the use of 8.1 electroacoustic music and acoustic instruments. The atmosphere will be conditioned with systems of movable panels, video beam projections, lights, and other gadgets, all synchronized with the music to enhance a more vivid experience.